2018
DOI: 10.1002/ece3.4543
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the parasitoid community associated with an outbreaking gall wasp,Zapatella davisae, and their relative abundances in New England and Long Island, New York

Abstract: Gall wasps (Hymenoptera: Cynipidae) are phytophagous insects that often go unnoticed; however, when they are introduced to a new area or released from their natural enemies, they have the capacity to outbreak and cause extensive foliar damage. One such outbreaking pest, Zapatella davisae (Cynipidae: Cynipini), causes significant damage and mortality to black oak, Quercus velutina, in the northeastern United States. In this study, we aimed to identify the parasitoid community associated with Z. davisae, compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Nevertheless, it is clear that the North American Sycophila is in need of taxonomic revision, and while this is beyond the scope of the current study, the molecular evidence presented here and in previous studies (Davis et al, 2018;Smith-Freedman et al, 2019) has shown that body coloration or wing band shape that was used by Balduf (1932) can vary significantly among conspecifics, and are therefore not reliable diagnostic characters. This is especially evident in species with a small wing band (e.g.…”
Section: Species Delimitation Of Sycophilamentioning
confidence: 70%
See 1 more Smart Citation
“…Nevertheless, it is clear that the North American Sycophila is in need of taxonomic revision, and while this is beyond the scope of the current study, the molecular evidence presented here and in previous studies (Davis et al, 2018;Smith-Freedman et al, 2019) has shown that body coloration or wing band shape that was used by Balduf (1932) can vary significantly among conspecifics, and are therefore not reliable diagnostic characters. This is especially evident in species with a small wing band (e.g.…”
Section: Species Delimitation Of Sycophilamentioning
confidence: 70%
“…Assessing species richness and revealing axes of host specialization for gall parasitoids requires a well-resolved and stable parasitoid taxonomy, which in turn requires an integrative approach. Single or multi locus approaches for taxon delimitation that use one or more genes such as the mitochondrial loci COI and Cytb have been used extensively to understand gall community diversity (Ács et al, 2010;Davis et al, 2018;Forbes et al, 2016;Gil-Tapetado et al, 2021;Kaartinen et al, 2010;MacEwen et al, 2020;Nicholls et al, 2018;Nicholls et al, 2010;Sheikh et al, 2021;Smith-Freedman et al, 2019;Ward et al, 2020;Weinersmith et al, 2020;Zhang Y.M. et al, 2014;2019a), often in combination with morphological and/or ecological data.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing species richness and revealing axes of host specialization for gall parasitoids requires a well-resolved and stable parasitoid taxonomy, which in turn requires an integrative approach. Single or multi-locus approaches for taxon delimitation that use genes such as the mitochondrial loci COI and Cytb have been used extensively to understand gall community diversity (Ács et al, 2010;Davis et al, 2018;Forbes et al, 2016;Gil-Tapetado et al, 2021;Kaartinen et al, 2010;MacEwen et al, 2020;Nicholls et al, 2018;Nicholls et al, 2010;Sheikh et al, 2022;Smith-Freedman et al, 2019;Ward et al, 2020;Weinersmith et al, 2020;Zhang Y.M. et al, 2014;2019a), often in combination with morphological and/or ecological data.…”
Section: Introductionmentioning
confidence: 99%
“…Some described North America species have a wide host repertoire (e.g., Sycophila quercilanae = 19 gaLL types on various oak species, S. occidentalis = 12, S. varians = 11, S. dorsalis = 9), though lack of detailed study suggests that these host repertoires are probably underestimates, and they are low compared to some Western Palearctic species in oak galls (e.g., Sycophila biguttata = 80, S. variegata = 41; Askew et al, 2013; Balduf, 1932; Noyes, 2019). The high level of sexual dimorphism, morphological plasticity and poorly known biology have further confounded species delimitation within this group (Davis et al, 2018; Gómez et al, 2013; Li et al, 2010; Lotfalizadeh et al, 2008; Smith‐Freedman et al, 2019). An inability to reliably identify Sycophila greatly hampers our understanding of the ecology and evolutionary history of their interactions with host galls, and also limits our understanding of Sycophila serving as potential biocontrol agents of pestiferous gall wasps such as the invasive Asian chestnut gall wasp, Dryocosmus kuriphilus (Dorado et al, 2020), or the North American species Zapatella davisae , which damages black oaks in the New England area (Davis et al, 2018; Smith‐Freedman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation